2014
DOI: 10.3177/jnsv.60.269
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Vitamin D Deficiency in Early Pregnancy Is Not Associated with Gestational Diabetes Mellitus Development or Pregnancy Outcomes in Korean Pregnant Women in a Prospective Study

Abstract: Gestational diabetes mellitus (GDM) is a worldwide, growing complication during pregnancy (1). Many risk factors for GDM have been identified, including obesity prior to and during pregnancy, older maternal age, previous history of GDM, and family history of diabetes (1). However, these risk factors are not sufficient to predict GDM development in almost half of all cases (2). Hence, it is necessary to identify other risk factors, including potential nutritional factors.Vitamin D deficiency has recently been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
39
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 26 publications
9
39
1
Order By: Relevance
“…We found a non-linear threshold effect of total To our knowledge, only one study has investigated the longitudinal profiles of serum 25(OH)D during pregnancy (at 12-14, 20-22, and 32-34 weeks) and prospectively examined the associations between trimester-specific vitamin D status and GDM in a cohort of 523 Korean women. 32 Similar to our study, there was no statistically significant difference in 25(OH)D between GDM cases and controls at any time points. However, they did not examine the associations between GDM risk and longitudinal changes of 25(OH)D levels, as well as other vitamin D biomarkers.…”
Section: Discussionsupporting
confidence: 88%
“…We found a non-linear threshold effect of total To our knowledge, only one study has investigated the longitudinal profiles of serum 25(OH)D during pregnancy (at 12-14, 20-22, and 32-34 weeks) and prospectively examined the associations between trimester-specific vitamin D status and GDM in a cohort of 523 Korean women. 32 Similar to our study, there was no statistically significant difference in 25(OH)D between GDM cases and controls at any time points. However, they did not examine the associations between GDM risk and longitudinal changes of 25(OH)D levels, as well as other vitamin D biomarkers.…”
Section: Discussionsupporting
confidence: 88%
“…All the results were higher in the GDM group. These findings are consistent with the study from Korea, where Park et al reported significant difference between GDM group and non-GDM group regarding several glucose measurements (Park et al, 2014). Also Parildar et al from turkey reported significant difference between GDM group and non-GDM group regarding HbA1c (p=0.004) and Fasting serum glucose (p<0.01) (Parildar et al, 2013).…”
Section: Data Are Presented As Mean +/-Sd (Minimum -Maximum)supporting
confidence: 82%
“…In a similarly replete population, investigators found no association between vitamin D status and pregnancy outcomes including pre-eclampsia, SGA, preterm birth and GDM (20) . However, in vitamin D-deficient populations, no association between 25-hydroxyvitamin D concentration and SGA (30) and GDM (22) was found ( Table 3).The main limitation to our study was the comparatively low prevalence of late pregnancy disorders, particularly GDM; this was due to the purpose for which SCOPE was established -that is, to investigate predictors of late pregnancy disorders in early pregnancy in low-risk, nulliparous women (12) . We did not have data on sunlight exposure -a factor that contributes most to 25-hydroxyvitamin D concentration.…”
mentioning
confidence: 82%
“…Although 23 % of Auckland SCOPE participants were vitamin D deficient (25-hydroxyvitamin D <50 nmol/l), half to more than 90 % of pregnant women have been found to be deficient in previous studies (20)(21)(22) . The SCOPE Auckland cohort may be more vitamin D replete in comparison with the obstetric Auckland population and the wider New Zealand population.…”
Section: Discussionmentioning
confidence: 99%